SIKAP INDUK SEMANG KOMUNITAS NELAYAN KOTA BENGKULU TERHADAP UNDANG-UNDANG PERLINDUNGAN DAN PEMBERDAYAAN NELAYAN - Yessilia Osira; Desy Afrita; Ika Pasca Himawati (UNIVED PRESS, Universitas Dehasen Bengkulu, 2017)
The attitude of fishermen community’s employers in Bengkulu city toward Institution Number 7 on 2016 about protection and empowerment for fishermen of fish farmers and salt fond farmers, basically was an early image of how process and content of the institution could encourage actively participation on efforts of fishermen community’s protection and empowerment, especially in Bengkulu city. The research with descriptive qualitative approach was conducted by interview and observation toward 15 employer informants in 3 areas, there were in Pantai Jakat, Kampung Bahari and Malabero areas of Bengkulu City. The research result shows that generally the employers in Bengkulu City can be divided into 1) employer of ship owner, consist of employer whose actively and not actively sailing 2) employer as collector of fisherman catch result from sailing, both for sold directly or became processed food. The research result also indicates that although the employers did not know exactly the process of making and content of the Institution of protection and empowerment of fishermen, but they understand the risk and susceptibility life of fishermen community, because basically they are also part and parcel of the fishermen life. This case makes them support and agree the issuance of Institution of protection and empowerment of fishermen. The employers hoped that there is socialization of the institution so they can participate on the implementation of Institution Number 7 on 2016 about protection and empowerment for fishermen of fish farmers and salt fond farmers. Keywords: Employer, Protection And Empowerment Of Fishermen